Reading habits and consumption in mother tongue and foreign language of pre-service primary school teachers at the University of Málaga - Castillo-Rodríguez, Cristina Milagrosa; Santos-Díaz, Inmaculada Clotilde (UMA Editorial, 2022)
Reading in a foreign language (FL) is a practice that should be essential for both pre-service and in-service teachers, since it contributes to acquire pedagogical, technical, and social knowledge, and to improve their linguistic competence in that language. This study aims to know the reading habits and consumption of pre-service teachers’ mother tongue and FL. A quantitative observational method was applied. The data were collected from an online survey administered to 388 students enrolled in the Degree of Primary Education at the University of Málaga during the academic years 2019/2020 and 2020/2021. Results showed a great difference between the time spent in reading in their mother tongue (Spanish) and in their first FL, and second FL. The type of reading most used during the last year has been through social networking sites, above all through Instagram and Twitter, while the least used was newspapers. Besides, it has been demonstrated that reader students had less difficulties in the linguistic skills and had a higher level of FL. These outcomes invite us to reflect upon the importance of promoting reading in FL for both academic and pleasure purposes from the beginning of their language learning.
Keywords: Investigación activa en educación; Profesores - Formación profesional; Lengua inglesa - Estudio y enseñanza; Comprensión lectora; Teacher training; Reading habit; Reading consumption; Language teaching